Tax planning and compliance for tax-exempt organizations rules, checklists, and procedures2014 cumulative supplement - Blazek, Jody; Adams, Amanda (John Wiley & Sons, 2014)
The cumulative supplement to the Tax Planning and Compliance for Tax-Exempt Organizations, 5th Edition Nonprofit organizations including health and welfare organizations, colleges and universities, private foundations, churches, libraries, museums, cultural institutions, and other smaller groups contend daily with the possibility of losing their tax-exempt status. This update contains clear-cut answers to all procedural and tax process questions. Here, you'll find straightforward information on changing Unrelated Business Income (UBI) rules, joint ventures, sponsorships, deductions against UBI, preparation of IRS forms, and more. Includes checklists and complete citations.
Includes bibliographical references and index. - Print version record
Keywords: Nonprofit organizations -- Taxation -- Law and legislation -- United States; Tax planning -- United States; Tax exemption -- United States; Planification fiscale; États-Unis; Impôt; Exemptions; États-Unis; Nonprofit organizations; Taxation; Law and legislation; Tax exemption; Tax planning; United States